Augmented reality in ocean’s secrets: educational application with attached book for students - Kasinathan, Vinothini; Al-Sharafi, Afnan Taha Abdullah; Zamnah, Aida; Appadurai, Naresh Kumar; Thiruchelvam, Vinesh; Mustapha, Aida (Linguistics and Culture Review, 2021)
The aim of this paper is a project which uses of Augmented Reality (AR) as a method for edutainment learning instrument to promote and encourage learning among students in this pandemic period. An AR application is developed together with a physical book called the Ocean’s Secret. This application projects animated 3D models of the sea animals as visualized in the printed book as the students or readers interact with the book. The book Ocean’s Secret offers facts about the ocean and marine animals along with fun quizzes, puzzles, coloring activities, as well as educational videos prompted by the AR objects. This book would be a good source as a learning tool during this last 2 years of the pandemic period. AROS application is evaluated via User Acceptance Test and an Observation Study. The findings show that the application has effectively aided online learning and make the learning environment more interesting and engaging. It is hoped that AR education books will assist online education in this pandemic period while at the same time offering students with the sense of excitement they desire.